Nrf2−/− regulated lung DNA demethylation and CYP2E1 DNA methylation under PM2.5 exposure - Wu, Mengjie; Jiang, Menghui; Ding, Hao; Tang, Siying; Li, Daochuan; Pi, Jingbo; Zhang, Rong; Chen, Wen; Chen, Rui; Zheng, Yuxin; Piao, Jinmei (Frontiers in Genetics, 2023)
Cytochrome P450 (CYP450) can mediate fine particulate matter (PM2.5) exposure leading to lung injury. Nuclear factor E2-related factor 2 (Nrf2) can regulate CYP450 expression; however, the mechanism by which Nrf2-/- (KO) regulates CYP450 expression via methylation of its promoter after PM2.5 exposure remains unclear. Here, Nrf2-/- (KO) mice and wild-type (WT) were placed in a PM2.5 exposure chamber (PM) or a filtered air chamber (FA) for 12 weeks using the real-ambient exposure system. The CYP2E1 expression trends were opposite between the WT and KO mice following PM2.5 exposure. After exposure to PM2.5, CYP2E1 mRNA and protein levels were increased in WT mice but decreased in KO mice, and CYP1A1 expression was increased after exposure to PM2.5 in both WT and KO mice. CYP2S1 expression decreased after exposure to PM2.5 in both WT and KO groups. We studied the effect of PM2.5 exposure on CYP450 promoter methylation and global methylation levels in WT and KO mice. In WT and KO mice in the PM2.5 exposure chamber, among the methylation sites examined in the CYP2E1 promoter, the level of CpG2 methylation was the opposite trend to CYP2E1 mRNA expression. The same relationship was evident between CpG3 unit methylation in the CYP1A1 promoter and CYP1A1 mRNA expression and between CpG1 unit methylation in the CYP2S1 promoter and CYP2S1 mRNA expression. This data suggests that methylation of these CpG units regulates the expression of the corresponding gene. After exposure to PM2.5, the expression of the DNA methylation markers ten-eleven translocation 3 (TET3) dioxygenase and 5-hydroxymethylcytosine (5hmC) was decreased in the WT group but increased in the KO group. In summary, changes in CYP2E1, CYP1A1, and CYP2S1 expression in the PM2.5 exposure chamber of WT and Nrf2-/- mice might be related to the specific methylation patterns in their promoter CpG units. After exposure to PM2.5, Nrf2 might regulate CYP2E1 expression by affecting CpG2 unit methylation and induce DNA demethylation via TET3 expression. Our study revealed the underlying mechanism for Nrf2 to regulate epigenetics after lung exposure to PM2.5.